The development and validation of Assessment Practices of Mathematical Thinking (APMT) instrument - Alhunaini, Saoud; Kamisah Osman,; Abdurab, Naser (Penerbit Universiti Kebangsaan Malaysia, 2020)
Assessment practices of mathematical thinking are an important part of mathematics teachers’ practices. This survey aimed to develop and validate an Assessment Practices of Mathematical Thinking (APMT) instrument. A total of 523 mathematics teachers from Omani public schools were randomly selected as samples. The initial scale consisted of 25 items. The scale was validated by experts in mathematics education and educational measurement and evaluation. Exploratory and confirmatory factor analysis was used to test the APMT model. Results show that the goodness-of-fit indices for the first and second order of the APMT model are placed within the acceptable criteria, and that the magnitudes of loadings for all items are statistically significant. The final version of the APMT scale contains five factors and 21 items. In conclusion, this study has developed an APMT instrument is acceptable psychometrically, and useful to be used for assessing teachers’ assessment practices of mathematical thinking in Arabic context, especially in Oman. The instrument can also be used by teachers for the purpose of self-assessment of their assessment practices of mathematical thinking, which can show their strengths and weaknesses. This instrument is unique because it focuses on different types of assessment practices that can be implemented to evaluate and develop students’ mathematical thinking within and out of the classroom.